2019
DOI: 10.1039/c9md00140a
|View full text |Cite
|
Sign up to set email alerts
|

Iridium piano stool complexes with activity againstS. aureusand MRSA: it is past time to truly think outside of the box

Abstract: Iridium based antimicrobial agents have shown efficacy against S. aureus, including MRSA, and appear to be safe in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Investigations into the cytotoxicity of the iridium Cp* diamine complexes were encouraging, with no toxicity observed against Vero or human embryonic kidney cell lines at concentrations at least 50 times higher than that of the minimum inhibitory concentrations. Additional in vivo toxicity screenings on a group of adult outbred white mice showed no detrimental side effects 14 days after administering a single IV dose (2.5 or 5 μg/kg), and a subsequent ICP-OES analysis found practically no iridium in the blood, heart, or lungs of the mice, with most of the iridium localized in the kidneys or excreted as urine …”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Investigations into the cytotoxicity of the iridium Cp* diamine complexes were encouraging, with no toxicity observed against Vero or human embryonic kidney cell lines at concentrations at least 50 times higher than that of the minimum inhibitory concentrations. Additional in vivo toxicity screenings on a group of adult outbred white mice showed no detrimental side effects 14 days after administering a single IV dose (2.5 or 5 μg/kg), and a subsequent ICP-OES analysis found practically no iridium in the blood, heart, or lungs of the mice, with most of the iridium localized in the kidneys or excreted as urine …”
Section: Introductionmentioning
confidence: 68%
“…Additional in vivo toxicity screenings on a group of adult outbred white mice showed no detrimental side effects 14 days after administering a single IV dose (2.5 or 5 μg/kg), and a subsequent ICP-OES analysis found practically no iridium in the blood, heart, or lungs of the mice, with most of the iridium localized in the kidneys or excreted as urine. 21 In order to advance the rapidly growing interest in the biological properties of metal NHC complexes, in this article we report the synthesis, characterization, and antimicrobial activities of Rh III and Ir III piano-stool complexes featuring a series of Cp* R and NHC ligands (Figure 4, bottom). Since the antimicrobial properties of these particular complexes have been understudied up to this point, this work features a wide scope of Cp* R substituents and NHC ligands to further the understanding of structure−activity relationships across noblemetal piano-stool complexes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Through ICP-OES it was shown that the iridium compounds were excreted efficiently through their urine and no iridium was detectable following sacrifice of the mice on day 14. No data on in vivo efficacy was reported in this study [102].…”
Section: Iridiummentioning
confidence: 82%
“…Complex inactivation may stem from halide dissociation over time to give an inactive cationic or dicationic metal complex [55]. Salt supplementation, such as with NaCl or KCl, Alternatively, the complexes may act directly on the viral proteins of the virion.…”
Section: Discussionmentioning
confidence: 99%